Tracing the historical and conceptual evolution of multifunctional landscapes - Garcia Conejero, Elena; Moreno Vargas, Diana; Vanegas Cubillos, Martha; Castro Nunez, Augusto (2025)
his report identifies the dominant theoretical frameworks, methodological approaches, and thematic trends shaping the Multifunctional Landscapes Framework (MFL) as a tool for territorial planning and decision-making, while highlighting persistent gaps and emerging opportunities for transformative, equity-oriented, and context-driven research and practice.